2000
DOI: 10.1128/mcb.20.20.7693-7705.2000
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Conidiation and Adenylyl Cyclase Levels by the Gα Protein GNA-3 in Neurospora crassa

Abstract: We have identified a new gene encoding the G protein ␣ subunit, gna-3, from the filamentous fungus Neurospora crassa. The predicted amino acid sequence of GNA-3 is most similar to the G␣ proteins MOD-D, MAGA, and CPG-2 from the saprophytic fungus Podospora anserina and the pathogenic fungi Magnaporthe grisea and Cryphonectria parasitica, respectively. Deletion of gna-3 leads to shorter aerial hyphae and premature, dense conidiation during growth on solid medium or in standing liquid cultures and to inappropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
169
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(192 citation statements)
references
References 86 publications
22
169
0
1
Order By: Relevance
“…This finding is similar to the DGPA2 mutant of S. pombe and to the defect observed in the corresponding Dgna-3 mutant from N. crassa, indicating that activation of this pathway might be an essential step in the germination process (Kays et al 2000;Hatanaka and Shimoda 2001). Interestingly, the corresponding Dgna-3 mutant from N. crassa develops smaller perithecia that are submersed in the agar (Kays et al 2000), a phenotype that was not observed in the corresponding S. macrospora mutant, but in the Dsac1 disruption strain. The differences between Dgsa1, Dgsa2, and Dgsa3 mutants suggest that they are involved in different steps of sexual development, such as fruiting body development and germination of the ascospores.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This finding is similar to the DGPA2 mutant of S. pombe and to the defect observed in the corresponding Dgna-3 mutant from N. crassa, indicating that activation of this pathway might be an essential step in the germination process (Kays et al 2000;Hatanaka and Shimoda 2001). Interestingly, the corresponding Dgna-3 mutant from N. crassa develops smaller perithecia that are submersed in the agar (Kays et al 2000), a phenotype that was not observed in the corresponding S. macrospora mutant, but in the Dsac1 disruption strain. The differences between Dgsa1, Dgsa2, and Dgsa3 mutants suggest that they are involved in different steps of sexual development, such as fruiting body development and germination of the ascospores.…”
Section: Discussionsupporting
confidence: 71%
“…These two features indicate that GSA1, just like its N. crassa counterpart, is evolutionarily related to the Ga i -subfamily of mammals that inhibits adenylyl cyclase (Ivey et al 1996). As already shown by others, the amino acid sequences for Ga-subunits are highly homologous within filamentous fungi (Bö lker 1998; Kays et al 2000;Parsley et al 2003). The proteins encoded by gsa1, gsa2, and gsa3 from S. macrospora display significant identities to corresponding proteins from other fungi with the highest amino acid identity to the Ga-subunits from N. crassa (data not shown).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The Ga proteins can be classified into three major subgroups: I, which inhibit adenylate cyclase; II, which have no homology with mammalian G proteins; and III, which in most fungi stimulate adenylate cyclase. In filamentous fungi, heterotrimeric G protein signalling pathways are involved in sporulation, mating, pathogenicity, secondary metabolite production, and vegetative incompatibility (Kays et al, 2000;Rosén et al, 1999;Horwitz et al, 1999;Loubradou et al, 1999).…”
Section: Role Of Heterotrimeric G Proteins In Conidiationmentioning
confidence: 99%
“…Growth rate, hyperosmotic sensitivity, conidiation, heterokaryon formation, and CAT fusion assays: Apical extension rates, hyperosmotic sensitivity, morphology of submerged cultures, and growth in standing liquid cultures were examined as previously described (Ivey et al 1996;Kays et al 2000;Kim and Borkovich 2004). Formation and fusion of conidial anastomosis tubes were assayed (Fleissner et al 2005;Kim and Borkovich 2006).…”
Section: Phenotypic Analysis 'mentioning
confidence: 99%